A 4-Benzene-Indol Derivative Alleviates LPS-Induced Acute Lung Injury Through Inhibiting the NLRP3 Inflammasome - Li, Junmei; Bai, Yang; Tang, Yiting; Wang, Xiangyu; Cavagnaro, María José; Li, Ling; Li, Zhaozheng; Zhang, Yi; Shi, Jian (Frontiers in Immunology, 2022)
Acute lung injury (ALI) is a common complication of critical illness that could frequently lead to acute respiratory distress syndrome and other serious clinical consequences. Sepsis is one of the major and most common inducements among all causes of ALI. Due to its high incidence and mortality rate as well as the complexity in treatment, sepsis-related ALI has become an urgent clinical problem waiting to be solved effectively. At present, only the protective ventilation strategy, restrictive fluid management and antibiotics application are measures that can improve the prognosis with evidence-based medical proof. No pharmacological treatment is currently available to protect or significantly reverse the prognosis. Seeking for effective interventions measures for sepsis-related ALI is one of the most necessitous research directions. In this research, a conspicuous discovery of treatment-related translational use for a 4-benzene-indol derivative was elaborated by screening a large number of chemical compounds. The results showed that 4-benzene-indol derivative could not only suppress the activation of NLRP3 inflammasome both in vitro and alleviate LPS-induced ALI in vivo, but also suppress the NLRP3 inflammasome in human myeloid leukemia mononuclear cells (THP-1) cell lines. Mechanistically, 1,2-diol blocks the NLRP3 inflammasome activation by disrupting NLRP3-NEK7 interaction and the subsequent NLRP3 inflammasome assembly and activation. To summarize, this research indicated that the newly-discovered 4-benzene-indol derivative targets NLRP3 inflammasome signaling, which consequently alleviates sepsis-related ALI. Collectively, the 4-benzene-indol derivative may serve as a potential therapeutic drug and NLRP3 inflammasome signaling would be a novel pharma-ceutical target for clinical treatment of sepsis-related ALI.